2017
DOI: 10.1016/j.socec.2017.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality experiments in economics

Abstract: The paper provides a review of research using virtual reality as a laboratory tool in economics. It addresses the question of whether behavior in virtual environments is a valuable source of empirical evidence for economists. A typology of virtual reality experiments based on the difference between low-immersive (LIVE) and high-immersive virtual environments (HIVE) is proposed. It is argued that virtual reality experiments are framed field experiments, which allow testing the effect of contextual cues on econo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 60 publications
0
23
0
Order By: Relevance
“…For example, people gain an understanding about an issue, experience an emotional response, such as interest or worry, and actively respond by changing climaterelevant behavior or political action. Research has shown that the content of the message [7,8], and level of visual immersion [9][10][11] can have an impact on the intensity of emotional responses and influence behavior [12]. Recently the nature documentary series Our Planet has received a plethora of media attention for the use of the negative framing of human-induced climate change impacts on nature which the series uses to push viewers toward a conservation website "to discover what we need to do now to protect our jungles" [13].…”
Section: Introductionmentioning
confidence: 99%
“…For example, people gain an understanding about an issue, experience an emotional response, such as interest or worry, and actively respond by changing climaterelevant behavior or political action. Research has shown that the content of the message [7,8], and level of visual immersion [9][10][11] can have an impact on the intensity of emotional responses and influence behavior [12]. Recently the nature documentary series Our Planet has received a plethora of media attention for the use of the negative framing of human-induced climate change impacts on nature which the series uses to push viewers toward a conservation website "to discover what we need to do now to protect our jungles" [13].…”
Section: Introductionmentioning
confidence: 99%
“…Academically, recent research efforts have begun to use more sophisticated techniques, such as eye tracking and choice simulations for complex problems (Glazer, 2012). Though VR has been broadly applied in various domains (Fox et al, 2009), including psychology (Washburn, 2003;Young, 2010), ethics (Cram et al, 2011), economics (Innocenti, 2017), and neuroscience (Parsons, 2015), much remains to be understood regarding how to use VR, what to expect from different VR applications, and what areas of VR need further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…From a pedagogical point of view, the cognitive-enhancement capabilities provided by VR/AR technologies have been studied in many fields such as economics (Innocenti 2017) neurosurgery (Pelargos et al 2017), cultural tourism education (Chiao et al 2018) and pedagogy (Rau et al 2018), to cite a few. In the AEC field, attention has also been paid to the pedagogical benefits that VR/AR technologies provide.…”
Section: Vr/ar In Research and Educationmentioning
confidence: 99%